Buyer opportunism in strategic supplier relationships: Triggers, manifestations and consequences. Issue 2 (March 2020) - Gelderman, Cees J.; Semeijn, Janjaap; Verhappen, Mark
Abstract: Opportunistic behavior is a well-known reason for the failure of collaborative buyer-supplier relationships. Despite the numerous studies on opportunism in buyer-supplier relationships, the individual level is largely understudied. We explore opportunistic behavior of purchasing professionals in strategic supplier relationships, focusing on triggers, manifestations and consequences. The Critical Incident Technique (CIT) was employed to interview professional purchasers in the Netherlands about their personal opportunistic behavior. This resulted in rich descriptions of 29 critical incidents of opportunistic buyer behavior, extracting first-hand information. We identified triggers that provoked purchasing professionals to behave opportunistically. These triggers are linked to specific manifestations and consequences. Highlights: We investigated buyer opportunism in strategic supplier relationships at the individual level. The study is the first to use the Critical Incident Technique for exploring opportunistic buyer behavior. We identified specific configurations of triggers, manifestations, and consequences of buyer opportunism. Buyer opportunism is most often a conscious choice, based on balanced assessments of risks and consequences.